Characteristics of the Small Bowel Lesions Detected by Capsule Endoscopy in Patients with Chronic Kidney Disease - Harunobu Kawamura; Eiji Sakai; Hiroki Endo; Leo Taniguchi; Yasuo Hata; Akiko Ezuka; Hajime Nagase; Takaomi Kessoku; Eiji Yamada; Hidenori Ohkubo; Takuma Higrashi; Yusuke Sekino; et al. (Gastroenterology Research and Practice)
Obscure gastrointestinal bleeding (OGIB) is one of the common complications in patients with chronic kidney disease (CKD), especially those who are on maintenance hemodialysis (HD). However, little is known about the characteristics of the small-bowel lesions in these patients, or of the factors that could predict the presence of such lesions. Therefore we enrolled a total of 42 CKD patients (including 19 HD patients and 23 non-HD patients), and compared the incidence of the small-bowel lesions among two groups. Furthermore, to identify predictive factors for the presence of small-bowel lesions, we performed multivariate logistic-regression-analyses. The incidence of small-bowel vascular lesions was significantly higher in CKD patients than in age-and-sex matched non-CKD patients (P<0.001). On the other hand, there was any significant difference of the incidence of small-bowel lesions between HD and non-HD patients. In CKD patients, past history of blood transfusion (OR 5.66; 95% CI 1.10–29.1, P=0.04) was identified as an independent predictor of the presence of vascular lesions, and history of low-dose aspirin use (OR 6.00; 95% CI 1.13–31.9, P=0.04) was identified as that of erosive/ulcerated lesions. This indicated that proactive CE examination would be clinically meaningful for these patients.